2018
DOI: 10.1002/pits.22222
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of RtI implementation on reading achievement outcomes

Abstract: Because several studies have investigated student outcomes in schools implementing Response to Intervention (RtI), relatively little research has investigated the impact of implementation on students’ long‐term achievement outcomes (i.e., several years after exposure). The purpose of this study was to describe one elementary school's RtI implementation process and to examine students’ long‐term reading comprehension outcomes following their exposure to various phases of implementation. Four cohorts of students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(52 reference statements)
0
2
0
2
Order By: Relevance
“…This strategy aligns with a Response to Intervention model of instructional pedagogy, in which students are given increasingly specialised support as they show evidence of requiring it (Coyne et al., 2018). Previous research has indicated that, for students struggling to read in the context of whole-class instruction, intervention delivered in a small-group or individual instructional context is beneficial for literacy learning (Coyne et al., 2018; Grapin et al., 2018). Importantly, the WARL and WARN as employed in the present study are considered a starting point for responding to students’ demonstrated difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy aligns with a Response to Intervention model of instructional pedagogy, in which students are given increasingly specialised support as they show evidence of requiring it (Coyne et al., 2018). Previous research has indicated that, for students struggling to read in the context of whole-class instruction, intervention delivered in a small-group or individual instructional context is beneficial for literacy learning (Coyne et al., 2018; Grapin et al., 2018). Importantly, the WARL and WARN as employed in the present study are considered a starting point for responding to students’ demonstrated difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…DBDM is an iterative process by which teachers gather, examine and interpret different types of assessment data to identify student strengths and needs and then make decisions about evidence‐based instruction, intervention and implementation (Mertler, 2014). Research has indicated that when teachers are engaged in on‐going use of DBDM, instruction can positively impact student reading skills (e.g., Filderman et al, 2018) with the possibility of long‐term effects (Grapin et al, 2019). However, DBDM can be challenging for both teachers and schools as it involves a host of skills such as assessment literacy or a technical understanding of assessment and the ability to choose appropriate assessments, administer, score, interpret and communicate results (Brookhart, 2011) and an understanding of how to locate and implement evidence‐based reading materials.…”
mentioning
confidence: 99%
“…estudiantes obtuvieron mejores resultados en pruebas internas, es decir en el aula, tras haber participado de la instrucción en el modelo, además reportan haber aumentado su capacidad de razonamiento y resolución de problemas (Hite & McGahey, 2015;Fuentes, Crawford & Huscroft-D'angelo, 2017), así como en habilidades básicas de lectura (Grapin, Waldron & Joyce-Beaulieu, 2019;Jaeger, 2016).…”
Section: J) Resultados En Pruebas De Aula Y Estatales Algunos Estudio...unclassified
“…Por otro lado, Grapin, et al (2019) sugirieron que la implementación de RtI en los primeros grados de escolaridad puede traer mejoras en el rendimiento de la lectura a largo plazo en los estudiantes, particularmente en el área de comprensión. Sin embargo, este hallazgo se contrapone con otro estudio posterior en el que una gran proporción de estudiantes, contrario a lo que se esperaba, no mantuvo en nivel alcanzado en las habilidades básicas de lectura tras haber recibido intervención en RtI, sino que retrocedió por debajo de las expectativas de nivel de grado (Nelson, Van Norman & Parker, 2018).…”
Section: K) Resultados a Largo Plazounclassified